2013
DOI: 10.1002/pc.22501
|View full text |Cite
|
Sign up to set email alerts
|

Molding of PBO fabric reinforced thermoplastic composite to achieve high fiber volume fraction

Abstract: In fiber‐reinforced plastic materials, the fiber volume fraction is one of the most important parameters, and it strongly influences the composite properties. However, it is hard to improve impregnation and the fiber volume fraction in fiber‐reinforced thermoplastics because thermoplastic resins have high melt viscosities. This study explored a reformative solution impregnation method for molding fabric‐reinforced thermoplastic composites with a high fiber volume fraction. The fiber volume fraction was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In this study, to reduce the viscosity of thermoplastics to achieve higher impregnation between the fiber bundles and matrix resin, a solution impregnation molding method was used to prepare carbon fiber-reinforced thermoplastics (CFRTPs). 19 Tensile test, three-point bending test, and thermal performance test confirmed that the manufactured composites possessed excellent mechanical properties and high heat-resistant properties. A type of super engineering plastic with a higher molecular weight was also used to manufacture composite materials to further verify the versatility of this method.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study, to reduce the viscosity of thermoplastics to achieve higher impregnation between the fiber bundles and matrix resin, a solution impregnation molding method was used to prepare carbon fiber-reinforced thermoplastics (CFRTPs). 19 Tensile test, three-point bending test, and thermal performance test confirmed that the manufactured composites possessed excellent mechanical properties and high heat-resistant properties. A type of super engineering plastic with a higher molecular weight was also used to manufacture composite materials to further verify the versatility of this method.…”
Section: Introductionmentioning
confidence: 75%
“…The V f of the resulting composite was increased to over 60%, which is equivalent to that of fiber-reinforced thermosetting plastics. 19 Additionally, using the same method, we successfully prepared carbon fibers-reinforced polyester (CF/PET) composite. Likewise, the V f of the CF/PET composite material reached up to 63.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the static compression test and compression fatigue test, the effect of the material type of knitted skin and the carbon fiber content on the composite spring are investigated. [21] Finite element method is applied to further explore the stress evolution and deformation mechanism of composite springs under compression. In this study, we aim to develop a type of lightweight helical composite which could provide a replacement strategy of existing metal or unidirectional filament reinforced springs used in the engineering field.…”
Section: Introductionmentioning
confidence: 99%
“…Mathivanan et al investigated the impact of fiber volume on aluminum/GFRP hybrid laminate test coupons and found that high fiber volume increased the elastic modulus, yield stress, and ultimate strength of the hybrid laminate. These findings have led to the development of various methods and processes that increase fiber volume but not defects . When controlled to fulfill design tolerance ranges, fiber volumes may provide optimal composite structures.…”
Section: Introductionmentioning
confidence: 99%